Why Uber failed in China: a comparison of Uber and Didi Chuxing which based on sharing economy in non-western context, through Michael Porter’s theory. - Lin, Baihui (2017)
Sharing economy is becoming popular among the world. Ride-sharing industry is one of heat industry of sharing economy. Uber is the leader and advanced firm of ride- sharing industry. Uber grows and expands very fast in global world. However, after its expansion in China for a few years, it surprisingly failed and was defeated by Chinese local firm DiDi Chuxing. Uber sold its Chinese firm in exchange some stakes of DiDi Chuxing and then quit Chinese market. This dissertation aims to explore the reason why Uber failed in Chinese market and why DiDi Chuxing wined the competitive battle with Uber. To solve these question, Michael Porter’s theories of industry structure and generic strategy will be applied. In the meantime, how useful Porter's theories are for understanding competitive advantage in a non-Western context is also considered in this work. From the comparison of Uber and DiDi Chuxing's industry context and generic strategy of competitive advantage, the dissertation concludes that industry structure of ride-sharing industry and the result of battle of Uber and DiDi Chuxing. The battle can be clearly illustrated through Porter's five forces model and Porter's generic strategy. However, it also implicates that it is not enough to survive from this battle using Porter's theory.